2009
DOI: 10.1088/0022-3727/42/5/055209
|View full text |Cite
|
Sign up to set email alerts
|

A global model for SF6plasmas coupling reaction kinetics in the gas phase and on the surface of the reactor walls

Abstract: Gas phase and reactor wall-surface kinetics are coupled in a global model for SF6 plasmas. A complete set of gas phase and surface reactions is formulated. The rate coefficients of the electron impact reactions are based on pertinent cross section data from the literature, which are integrated over a Druyvesteyn electron energy distribution function. The rate coefficients of the surface reactions are adjustable parameters and are calculated by fitting the model to experimental data from an inductively coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 69 publications
0
45
1
Order By: Relevance
“…24 Another possible explanation for the observed phenomena could be based on chemical asymmetry of positive and negative ions: many radicals of SF 6 are formed in ICP discharge due to intense dissociation, and these radicals have different ionization and electron attachment rates. 13,25 Hence, the positive ion and negative ion fluxes might be composed of different species, for example from SF x þ (x ¼ 3,5) as positive ions and F À , SF 6 À as negative, 13 and their impact on the film growth and electrical behavior might therefore not be the same. In addition, one should always keep in mind that negative ion extraction from real ion-ion plasma is accompanied by a certain electron flow, so electron flux-stimulated deposition or polymerization may play an important role here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Another possible explanation for the observed phenomena could be based on chemical asymmetry of positive and negative ions: many radicals of SF 6 are formed in ICP discharge due to intense dissociation, and these radicals have different ionization and electron attachment rates. 13,25 Hence, the positive ion and negative ion fluxes might be composed of different species, for example from SF x þ (x ¼ 3,5) as positive ions and F À , SF 6 À as negative, 13 and their impact on the film growth and electrical behavior might therefore not be the same. In addition, one should always keep in mind that negative ion extraction from real ion-ion plasma is accompanied by a certain electron flow, so electron flux-stimulated deposition or polymerization may play an important role here.…”
Section: Discussionmentioning
confidence: 99%
“…8 The problems of film deposition and surface reactions in SF 6 -containing plasmas are periodically discussed in the literature. [9][10][11][12][13] One of the expected problems is therefore chamber corrosion and deposition of insulating film on the thruster walls, diagnostics and finally on the extraction system surface, causing an important problem namely lost of the beam acceleration. Unfortunately, deposition processes in pure ion-ion plasmas formed using SF 6 are still not well investigated and understood at the moment.…”
Section: Introductionmentioning
confidence: 99%
“…Electron collision reactions [6] Neutral-neutral reactions [24] C2F6 discharge Electron collision reactions [19] C4F8 discharge Electron collision reactions [25] Neutral-neutral reactions [25] Ion-ion reactions [25] SF6 discharge Electron collision reactions [26] Neutral-neutral reactions [26] Ion-neutral reactions [26] Ion-ion reactions [26] a…”
Section: Cf4/h2 Dischargesmentioning
confidence: 99%
“…In time, these insulation defects may escalate into insulation failure during operation, thus posing a risk to the safe and reliable operation of the equipment and the entire power grid [4]. Extensive studies [5,6] have reported that the SF 6 molecules crack to form low fluoride (SF x , x = 1, ..., 5) under partial discharge (PD) [5,6]. After long-term operation, different levels of trace moisture, oxygen, and other impurities may be present inside of GIS.…”
Section: Introductionmentioning
confidence: 99%